Pete the cat's groovy bake sale - Dean, James, 1957- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2018)
While trying to make something for the school bake sale, Pete seems to only be able to make a mess.
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Baking -- Juvenile fiction; Humorous stories; Cuisson au four -- Romans, nouvelles, etc. pour la jeunesse; Readers (Primary); Readers (primary).; readers; Humorous fiction; Humorous fiction; Readers (Publications); Lectures et morceaux choisis